2014
DOI: 10.7556/jaoa.2014.127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Somatic Dysfunction on Leg Length and Weight Bearing

Abstract: Specific pelvic and sacral somatic dysfunctions have the potential to influence leg lengths, leading to mild disparities in length and in weight-bearing distribution through the lower extremities. (ClinicalTrials.gov number NCT01097109).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…el reparto de peso era mayor en el retropié derecho (85.7%). de acuerdo con Qureshi et al (14). que demostró que los sujetos con dismetrías verdaderas mayores a 10 mm.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…el reparto de peso era mayor en el retropié derecho (85.7%). de acuerdo con Qureshi et al (14). que demostró que los sujetos con dismetrías verdaderas mayores a 10 mm.…”
Section: Discussionunclassified
“…Además, el peso no es compartido entre las dos extremidades, constituyendo un factor de riesgo para la degeneración de las articulaciones (9,11,13,14).…”
Section: Introductionunclassified
“…However, it has been demonstrated that there is no consistency in the relationship between sacral base declination and apparent leg length discrepancy. 7 In fact, most sacral base unleveling is associated with L5 segmental dysfunctions, not with sacroiliac shears. Interestingly, Qureshi et al found the superior sheared innominate to be more common than either anterior or posterior rotated innominates when side was not considered and the left superior sheared innominate to be the most common innominate dysfunction overall.…”
Section: Possible Causes Of Innominate Shearmentioning
confidence: 99%
“…7 A projection from the iliac side with a concomitant sacral indentation is sometimes noted at S2 and is considered the pivot area for sacral nutation and counternutation. 7 In addition to the expected joint capsule enclosing the whole joint, there are a number of transverse supporting ligaments both anterior to the joint and posterior. Relatively, the posterior ligaments are among the thickest and strongest in the body.…”
Section: Anatomy Of the Sacroiliac Jointmentioning
confidence: 99%
See 1 more Smart Citation